Tingkat Pengetahuan dan Perilaku Swamedikasi pada Mahasiswa Universitas Mulawarman: Knowledge and Behavior of Swamedication in Mulawarman University Students - Maria Simanjuntak; Wisnu Cahyo Prabowo; Adam M. Ramadhan (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Self-medication is the process of self-medication by a person without using a prescription from a doctor. Self-medication is one of the many efforts made by the community in overcoming minor illnesses. One of the factors that can influence self-medication behavior is knowledge about self-medication. This study was conducted to determine the level of knowledge and behavior of self-medication in students at Mulawarman University. This type of research is an observational research qualitatively and quantitatively using an online questionnaire. Respondents obtained as many as 929 respondents. The results of the research on the characteristics of respondents obtained the highest percentage of age 21 years (36.7%), class of 2017 (46.8%), and female gender (77.5%). The results showed that 43.4% of respondents had good self-medication knowledge and 60% of respondents had good self-medication behavior. The results of statistical tests using the Spearman Rank method show that there is a significant relationship between the level of knowledge and self-medication behavior. The significance value (p) obtained is 0.000, with a correlation coefficient of 0.270 in the health faculty student group and 0.212 in the non-health faculty student group which shows the close relationship between the two variables is weak.